PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR (POC) DARI PELEPAH PISANG DAN KOMPOS BERBAHAN KOTORAN KAMBING SERTA SEKAM PADI SEBAGAI ALTERNATIF PUPUK ORGANIK RAMAH LINGKUNGAN - Arif Sobirin; Khafid Mahbub; M. Irji Maulana Saputra; Intan Amali Nurawalia; Keysa Naysilla Agustine; Sri Ida Dewi; Fika Setiani; Risqi Khamdhina Khoirunisa; Kharissa Risqi Wulandari; Rara Amelia; Helmilia Agistina; Muhammad Arsyad Maulana (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The utilization of agricultural and livestock waste as organic fertilizer remains limited, although banana stalks, goat manure, and rice husks are abundantly available in Kajongan Village, Kajen District. This community service program aimed to improve the knowledge and skills of farmer group members in producing liquid organic fertilizer (LOF) from banana stalks and compost from goat manure and rice husks as environmentally friendly fertilizer alternatives. The program consisted of problem identification, activity preparation, pre-test, education and socialization, demonstration and hands-on practice, post-test, mentoring, and evaluation. A total of 25 farmer group members participated in the activity. The evaluation showed an increase in the average knowledge score from 55 in the pre-test to 85 in the post-test. Furthermore, all participants successfully practiced the independent production of liquid organic fertilizer and compost. The program effectively enhanced participants' capacity to utilize organic waste as environmentally friendly fertilizer and supported the implementation of sustainable agriculture.